The Impact of the Project-Based Learning Model on Students Collaboration Skills in Social Studies Learning at the Elementary School Level - Binggo, Fandi H (Newinera Publisher, 2025)
This study examines the effectiveness of the Project-Based Learning (PjBL) model in enhancing students' collaboration skills in Social Studies (IPS) education at the elementary school level. Using a one-group pretest-posttest experimental design, the study involved 20 students at SD Laboratorium UNG. Students' collaboration skills were measured before and after the implementation of PjBL through pretest and posttest assessments. Statistical analysis using paired samples t-test and Cohen's d was conducted to evaluate the significance and effect size of the observed changes. The results indicated a significant improvement in collaboration skills, as reflected in the increase of the average score from 53.1 on the pretest to 69.45 on the posttest. Additionally, Cohen's d value of 2.20 indicated a large effect size, confirming that PjBL not only significantly enhanced students' collaboration skills but also provided a practical and impactful learning experience. This study concludes that PjBL is a highly effective method for enhancing collaboration skills in Social Studies education, preparing students to face challenges in both educational and professional settings.